A philosophical approach to aligning strength and conditioning support to a coaches' performance model: A case study from a national rowing performance programme - Rawlley-Singh, I.; Wolf, A. (International Journal of Sports Science & Coaching, 2023)
Coaches within the same sport often have varying methods to achieve performance outcomes, and, therefore, it is crucial to understand their performance model to maximise the impact of strength and conditioning (S&C) support. Having a deliberate approach for understanding the demands of a sport from a sports coach's lens and aligning S&C support to the coaches' performance model rather than utilising a generic needs analysis to guide S&C support is vital to provide impactful S&C support. The multi-disciplinary team (MDT) may also play a pivotal role in providing insight into various aspects of performance beyond a generic needs analysis. It is to the S&C coaches' advantage to utilise the expertise of the MDT. Finally, the S&C coach must develop a technical framework that consists of avenues of impact or objectives for S&C support and demonstrates how biomotor qualities developed within the S&C programme may support determinants of performance and technical models for key sporting actions, in line with the coaches' performance principles. The current paper aims to utilise the authors' experience of working with the head coach of two national rowing performance programmes over the last three Olympic cycles, with specific reference to the preparation for the 2020 Tokyo Olympic games to articulate a philosophical approach for aligning S&C support to a coach's performance model.